PENGARUH RASIO KEUANGAN DER, CR, ROA, EPS TERHADAP HARGA SAHAM PADA PERUSAHAN SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (STUDI KASUS PADA PERUSAHAAN SEMEN YANG TERDAFTAR DI BEI) - RORO PUSPA SARI, WEISTY (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this study is to determine the effect on stock prices of financialperformance in cement companies listed on the Stock Exchange in the period 2001-2011.Financial performance was measured by using a Debt to Equity Ratio (DER), Current Assets(CR), Return on Assets (ROA) and Earnings per Share (EPS). The results suggest thatfinancial performance is positive but not significant effect on stock prices on cementcompanies in Indonesia Stock Exchange. This is possible because the cement company’sstock price has been dominated by the market or its external factors such as the need forproduct development along with the development. While partially proved that the Debt toEquity Ratio (DER), Current Assets (CR), Return on Assets (ROA) dan Earning per Share(EPS) did not significantly influence stock prices. Then the t test results showed that allindicators of financial performance on a positive effect on stock prices unless Earning PerShare (EPS), this is possible because one of the cement company Indocement TunggalPrakarsa Tbk has data development in the year 2001-2010 which has increased Earning PerShare (EPS) which is not proportional to the increase in stock prices.Keyword : Debt to Equity Ratio (DER), Current Assets (CR), Return on Assets (ROA) danEarning per Share (EPS), Stock Price